2014
DOI: 10.1021/am5037687
|View full text |Cite
|
Sign up to set email alerts
|

Bending Induced Self-Organized Switchable Gratings on Polymeric Substrates

Abstract: In general, cracking of thin films is synonym of irreversible damage, delamination and/or device failure. Nevertheless, under certain well controlled conditions, a tensile stress applied to a supported film can induce the development of a regular pattern perpendicular to the resulting strain 11,12 . For example, patterns of cracks produced by uniaxial straining of plasma surface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Micro‐ and nanostructured soft surfaces offer a new strategy to dynamically tune optical properties by changing the surface topography without affecting the bulk properties . Recently, surface wrinkling has become a very cost‐effective, facile technology to reversibly control the surface topography, which inspired a wide range of applications such as thin‐film properties measurement, tunable adhesion and wettability, stretchable electronics, and optical materials/devices . Some more recently studies have demonstrated that surface wrinkling can also be used to prepare large‐area smart windows capable of controlling the light transmittance by means of micro‐ and nanopillar arrays on wrinkled elastomers, crumpling of metallic nanofilms, graphene films, and graphene oxide films on elastomeric substrates and silica nanoparticle‐embedded elastomer composite .…”
Section: Introductionmentioning
confidence: 99%
“…Micro‐ and nanostructured soft surfaces offer a new strategy to dynamically tune optical properties by changing the surface topography without affecting the bulk properties . Recently, surface wrinkling has become a very cost‐effective, facile technology to reversibly control the surface topography, which inspired a wide range of applications such as thin‐film properties measurement, tunable adhesion and wettability, stretchable electronics, and optical materials/devices . Some more recently studies have demonstrated that surface wrinkling can also be used to prepare large‐area smart windows capable of controlling the light transmittance by means of micro‐ and nanopillar arrays on wrinkled elastomers, crumpling of metallic nanofilms, graphene films, and graphene oxide films on elastomeric substrates and silica nanoparticle‐embedded elastomer composite .…”
Section: Introductionmentioning
confidence: 99%
“…The flat doublesided coated foil is transparent (central picture). The projected light reveals the pattern printed on the concave surface, whereas the pattern on the opposite convex surface remains invisible (left and right pictures)[507].…”
mentioning
confidence: 99%
“…One of the most common applications of optical diffusers is the backlighting system of the liquid crystal displays . More recently, emerging applications for optical diffusers such as smart windows and invisible labels have been demonstrated. In addition, light softening has found its way to optoelectronic devices such as solar cells, photodetectors, and light emitting diodes to enhance their power conversion efficiency, sensitivity, and brightness, respectively, through efficient photon management.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, polydimethylsiloxane (PDMS) is the material of first choice when it comes to flexible and tunable optical devices due to its superior optical transparency and mechanical properties. In particular, PDMS has recently attracted great attention for tunable optical diffusers and gratings . The proposed structures, however, require rather complicated and expensive fabrication processes including glancing angle deposition, surface wrinkling, E‐beam lithography and pattern transfer, and holographic lithography …”
Section: Introductionmentioning
confidence: 99%